La exclusión social y sus efectos en el aprendizaje de los estudiantes de la escuela de educación básica Dr. Antonio parra Velasco del rito. San Luis del cantón Mocache - García Parraga, Rosa Fanny (2015)
This applies to students of different educational institutions in many cases causing the imbalance in our society, for this reason, focus the theme of "social exclusion AND ITS IMPACT ON STUDENT LEARNING SCHOOL OF BASIC EDUCATION DR. Antonio Parra Velasco RCTO. SAN LUIS DEL Mocache Canton "is very important as it has been detected that there are different parallel students who are excluded in the process of learning becoming a serious problem for the institution and the educational community. In short, poor quality education affects everyone, and exclusion is not only in education but in society.